2018
DOI: 10.26710/jbsee.v4i2.244
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Conflict Management Style Between Malaysian and Thai Employees: A Case Study in Top Glove Corporation

Abstract: Objective: This study investigated the fundamental beliefs regarding cross-cultural differences in conflict styles. Methodology: The sample consisted of 46 employees from 2 different countries between Malaysia and Thailand.   T test analysis was used to investigate the effect of conflict styles on both Malaysia and Thai employees.  Results: Findings revealed that the avoiding and compromising styles are generally the most preferred by both Malaysian and Thai employees; accommodating and col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…This is accompanied by an equal growth of greenhouse gas emissions from developed and emerging countries (Qayyum et al, 2019). (Sahban and Abbas, 2018) research also showed the impact of high health risks in African countries on energy use and emissions of greenhouse gases. People's health is adversely affected by both indoor and outdoor contamination, which is exacerbated by the use of fossil fuels.…”
Section: R E T R a C T E Dmentioning
confidence: 98%
“…This is accompanied by an equal growth of greenhouse gas emissions from developed and emerging countries (Qayyum et al, 2019). (Sahban and Abbas, 2018) research also showed the impact of high health risks in African countries on energy use and emissions of greenhouse gases. People's health is adversely affected by both indoor and outdoor contamination, which is exacerbated by the use of fossil fuels.…”
Section: R E T R a C T E Dmentioning
confidence: 98%
“…Results confirm the Kyenizian consumption function for South Asian economies. The same outcomes were observed by [ 48 , 49 ]. Developing countries derive a significant portion of their national income from the export of basic products.…”
Section: Resultssupporting
confidence: 86%
“…After analyzing the dataset of questionnaires in the software, we have different options regarding the model specification; for example, the logit model (also known as Logistic Regression) and the probit model (Sahban and Abbas, 2018). However, due to the nature of the data, non-parametric techniques have been used to derive reliable results from this dataset.…”
Section: Methodsmentioning
confidence: 99%